2013
DOI: 10.1017/s1751731113001195
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and repeatability of milk coagulation properties predicted by mid-infrared spectroscopy during routine data recording, and their relationships with milk yield and quality traits

Abstract: The aim of this study was to estimate (co)variance components for milk coagulation properties (MCP) predicted by mid-infrared spectroscopy (MIRS) during routine milk recording, and to assess their relationships with yield and quality traits. A total of 63 470 milk samples from Holstein-Friesian cows were analyzed for MCP, pH and quality characteristics using MIRS. Casein to protein and protein to fat ratios were calculated from information obtained by MIRS. Records were collected across 1 year on 16 089 cows i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
38
4
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 32 publications
17
38
4
3
Order By: Relevance
“…Descriptive statistics of milk chemical composition and MY are in agreement with those documented in several studies on Italian Holstein − Friesian cows Pretto et al, 2011;Tiezzi et al, 2013), with the exception of SCS, which exhibited a smaller phenotypic coefficient of variation in the present study. Parity mean milk composition and yield (Table 2) were generally in agreement with other studied international populations of dairy cows (Ikonen et al, 2004;Hansen et al, 2006;Bastin et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Descriptive statistics of milk chemical composition and MY are in agreement with those documented in several studies on Italian Holstein − Friesian cows Pretto et al, 2011;Tiezzi et al, 2013), with the exception of SCS, which exhibited a smaller phenotypic coefficient of variation in the present study. Parity mean milk composition and yield (Table 2) were generally in agreement with other studied international populations of dairy cows (Ikonen et al, 2004;Hansen et al, 2006;Bastin et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Overall, prediction models in the present study were more accurate than reported by Dal and These prediction models are currently used in several milk laboratories in Italy to routinely provide milk coagulation phenotypes for genetic evaluations (Tiezzi et al, 2013;Penasa et al, 2014). The prediction of some innovative milk traits is quite difficult, especially when these traits are not strictly related to the mid-infrared energy absorption of specific chemical functional bounds (i.e., N-H bonds in protein or C-H bonds in lipids).…”
Section: Prediction Of Rennet Coagulation Traitssupporting
confidence: 53%
“…Milk lactose content was lower on HI than on LO (p < .001), but only in the multiparous cows (interaction, p < .001). However, this decline was without practical relevance from its magnitude (Tiezzi et al 2013). There was also a large decrease (p < .001) in MUN from LO to HI, which can be explained by excessive dietary CP content of the LO pasture compared to the HI pasture.…”
Section: Effect Of Highland Grazing and Parity On Milk Yield And Compmentioning
confidence: 92%